Embriogenesis dan Desikasi Embrio Somatik Jeruk Keprok Batu 55 (Citrus reticulata Blanco.) untuk Meningkatkan Frekuensi Perkecambahan - Fathur Rahmi, Atika; Purwito, Agus; Husni, Ali; Dinarti, Diny (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2017)
ABSTRACTIn vitro breeding technique of citrus is effective when optimum explant regeneration method is obtained. Low germination frequency and high abnormality were barrier in citrus somatic embryogenesis. This research aimed at optimizing somatic embryogenesis in Tangerine var. Batu 55. This research consisted of 3 experiments. First experiment was maturation of embryogenesis, using Completely Randomized Design (CRD) method. Modified MS+MW was used as basic media added with 500 mg L-1 malt extract (control) and addition of 3 mg L-1 BAP, and 2.5 mg L-1 ABA as treatments. Second experiment was SE (cotyledonary phage) desiccation. Factorial CRD used in two factors. First factor was poly-ethylene-glicol/PEG 8000 (0, 2.5, 5, 7.5 and 10%), while second factor was immersed periods (control, 3, 6, and 9 hours), in desiccant solution (base medium + PEG). Third experiment was studied of plantlet growth and development planlets. Based on CRD 2 factor method, the first factor was PEG concentrations from the second experiment. Second factor were active charcoal treatments (with or without), in basic media. The result showed that 2.5 mg L-1 ABA produced has highest mature somatic embryo (SE). Desiccation for 9 hours, induced the highestt germination frequencies (90.29%). The best growth of plantlets shown in previous experiments immersed desiccant PEG 2.5% for 9 hours, and cultured in basic media with 2 g L-1 of activated charcoal.Keywords: desiccant, embryogenic callus, maturation, PEG 8000, somatic embryo ABSTRAK Pemuliaan tanaman melalui teknik in vitro efektif bila metode regenerasi eksplan optimum telah diperoleh. Rendahnya frekuensi perkecambahan dan tingginya abnormalitas, menjadi kendala pada embriogenesis somatik jeruk. Penelitian terdiri atas 3 percobaan paralel, bertujuan mengoptimalkan metode embriogenesis somatik jeruk, khususnya Keprok Batu 55. Percobaan pertama pematangan kalus embriogenik menggunakan Rancangan Acak Lengkap (RAL) satu faktor, dengan perlakuan penambahan ZPT (kontrol, 3 mg L-1 BAP, dan 2.5 mg L-1 ABA) pada media dasar (MS modifikasi vitamin MW) diperkaya 500 mg L-1 ekstrak malt. Percobaan kedua desikasi embrio somatik (fase kotiledon) menggunakan RAL dua faktor. Faktor pertama konsentrasi poly-ethylene-glicol/PEG 8000 (0, 2.5, 5, 7.5 dan 10%), dan faktor kedua waktu perendaman (kontrol, 3, 6, dan 9 jam) pada larutan desikan (media dasar + PEG). Percobaan ketiga mempelajari pertumbuhan dan perkembangan planlet, menggunakan RAL dua faktor. Faktor pertama konsentrasi PEG planlet pada percobaan kedua, dan faktor kedua perbedaan media dasar (tanpa dan dengan arang aktif). Hasil percobaan menunjukkan penambahan 2.5 mg L-1 ABA menghasilkan maturasi embrio somatik terbaik. Desikasi 9 jam menghasilkan frekuensi perkecambahan 90.29%. Pertumbuhan terbaik ditunjukkan planlet yang pada percobaan sebelumnya direndam 9 jam desikan PEG 2.5%, dan dibesarkan pada media dasar dengan 2 g L-1 arang aktif.Kata kunci : desikan, embrio somatik, kalus embriogenik, PEG 8000, pematangan